Minimally invasive esophagectomy/ gastroesophagectomy for cancer - Long term results from a single institution - Thakur, Binay; Devkota, Mukti; Bhandari, Nikesh; Shrestha, Shashank; Kharel, Ashish (Nepalese Journal of Cancer, 2022)
Background: Esophagectomy is a complex operation. Minimally invasive esophagectomy (MIE) may decrease the morbidity and mortality of resection. The aim of this study was to produce long term outcome of MIE from a single center in Nepal.Methods: Patients with squamous cell carcinoma and adenocarcinoma of esophagus/ gastroesophageal junction who underwent MIE between 2001-2018 were analyzed.Results: 215 patients were taken for MIE during 2001-2018. There was 11.2% conversion rate. Totally MIE approach was performed in 43% cases and hybrid MIE in 57% cases. Mean operative time, intra operative blood loss, anastomotic leak, pulmonary infection, recurrent laryngeal nerve injury and in-hospital mortality were 246 min, 286 ml, 13.1%, 9%, 6.8% and 3%, respectively. Final histopathology revealed most common Stages III and IV in 51.2% and 36.1%, respectively. The median survival was 34 months and 5-OS was 27%. 5-OS was 27% and o% for R0 and R+ resection (p